The some questions of grammatical homonyms in Modern Karakalpak language - Ali Kaljanov (International Journal on Orange Technologies, 2020)
The concepts grammatical homonyms which are interpreted in linguistic as quite difficult and specific, have been investigated in this paper. The existing scientific opinions about these problems have been shown. In the process of communication homonyms sometimes lead to confusion and misunderstanding.